Media Sosial sebagai Penyebarluasan Informasi Pemerintah Aceh - Heri Juanda (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2017)
Social media is one of the most popular platform use by people now. The presence of social media rapidly open space interaction society in cyberspace. Public Relations and Protocol Bureau of the Aceh Goverment have an important role in disseminating government information to the public. This paper will discuss how Public Relation and Protocol Bureau of Aceh Government use social media in disseminating information of government activities using qualitative descriptive method with content analysis approach. The results show that in disseminating information to public, Public Relation and Protocol Bureau of aceh governtment use social media such as Facebook, Instagram, Twitter and YouTube to broadcast government information. The informations get responses and forms a positive image for the government.